Diminution of air pollution from NOX and smoke/soot emitted from alcohols/diesel blends in diesel engine and influence of the exhaust gas recirculation (EGR) - Fayad, Mohammed A.; Alani, Waleed K.; Dhahad, Hayder A.; Zheng, Jing (Journal of Environmental Engineering and Landscape Management, 2023)
In this study, the impact of butanol-diesel blends and exhaust gas recirculation (EGR) on engine performance, NOX emissions, smoke, and particulate matter (PM) characteristics were experimentally investigated under fuel post-injection condition. The maximum peak of cylinder pressure is achieved under without EGR compared with applied different rates of EGR. Furthermore, the brake thermal efficiency (BTE) increased during the combustion of B20 and B10 by 4.25% and 2.61%, respectively, compared with diesel fuel combustion. Considerable reductions in carbonaceous gas emissions (CO and THC) and nitrogen oxides (NOX) were achieved from combustion of B20 and B10 compared to the diesel fuel for with and without EGR. The NOX emissions decreased with 30% of EGR compared with 15% of EGR for all fuels studied. The results indicated that the addition butanol to the diesel fuel significantly reduced smoke opacity and soot emissions by 31.3% and 35.26%, respectively, compared with diesel. It is observed that an effective reduction of the NOX emissions to be higher during the combustion of B20 compared to the combustion of B10 and diesel for different EGR rates. The results of PM emission showed increase by 16% under 15% of EGR and 28% under 30% of EGR compared to the without EGR for all fuels tested. The number, concentration and size of PM decreased from combustion of B20 and B10 compared with diesel fuel combustion for with and without EGR.